2012
DOI: 10.4103/0976-500x.103686
|View full text |Cite
|
Sign up to set email alerts
|

The incidence and clinical relevance of drug interactions in pediatrics

Abstract: Objective:To investigate the prevalence of the major drug interactions in children and verify the rate and profile of drug interactions in hospitalized pediatric patients.Materials and Methods:A retrospective study was designed and data collected from the files of hospitalized children in Pulmonology, Nephrology, and Gastroenterology wards of a Pediatric Clinic, from July 1999 to 2004.Results:From the analyzed material, we detected 34 cases of interactions, of which 1 was pharmacodynamics interaction, 13 were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
2

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(24 citation statements)
references
References 12 publications
1
20
2
Order By: Relevance
“…In present study, the overall prevalence of DDIs was 16 % out of all DDIs. Prevalence rate was lower in compare to studies conducted by Feinstein et al 10 and Qorraj-Bytyqi et al, 12 they reported that paediatric patients exposed to DDI were 49% and 23% respectively. DDI severity criteria enhances decision making ability by assessing risk versus benefit alternatives.…”
Section: Decrease Sedative Effectcontrasting
confidence: 49%
See 1 more Smart Citation
“…In present study, the overall prevalence of DDIs was 16 % out of all DDIs. Prevalence rate was lower in compare to studies conducted by Feinstein et al 10 and Qorraj-Bytyqi et al, 12 they reported that paediatric patients exposed to DDI were 49% and 23% respectively. DDI severity criteria enhances decision making ability by assessing risk versus benefit alternatives.…”
Section: Decrease Sedative Effectcontrasting
confidence: 49%
“…In present study, maximum number of patients prescribed two drugs per prescription. Whereas, study done in Pakistan, 12 maximum number of patients had prescribed 4-6 drugs per prescription. The potential risk of DDIs increases with an increase number of drugs prescribed.…”
Section: Decrease Sedative Effectmentioning
confidence: 99%
“…These might result in higher risk of unsafe usage of medicines, declining the efficacy and increasing the overall price of treatment. Unfortunately, there are very few published studies carried out in Kosovo concerning drug use, side effects, drug - drug interactions (4, 9, 10, 11). This directly contributed to the main aims of this study, that are:…”
Section: Introductionmentioning
confidence: 99%
“…Based on definitions used in the literature, we defined DDI as "Pharmacologic or clinical response to the administration of a drug combination, different from that anticipated from the known effects of the two agents when given alone" 9 .…”
Section: Definitionsmentioning
confidence: 99%